Improved Design for LKJ Data Transfer Device - XU Suqiang (机车电传动)
By improving the existing design of LKJ data transfer device, LKJ data reloading terminal had good performance ofhuman-computer interaction, and accomplished the secret-key security authentication and multi-version date storage for LKJ datareloading , which resolved the on-site LKJ date reloading risk.